Breaking the Tradition: Exogamy Marriage in Tenganan village, Bali - Sudarma, I Putu (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In Tenganan Pegringsingan, marriage is very close because citizens can only marry under inbreeding. In contrast, exogamous marriage is strictly prohibited. When this prohibition is violated, the bride and groom are subject to adat restrictions. The reasons for applying the adat sanction to the marriage of exogamy are: preserve tradition, maintain the lineage system and balance. The types of adat sanctions are: on bail and moral. The implications of adat limitations include non-insurgency, lack of well-being and loss of rights.